2019
DOI: 10.3389/fimmu.2019.00583
|View full text |Cite
|
Sign up to set email alerts
|

TL1A (TNFSF15) and DR3 (TNFRSF25): A Co-stimulatory System of Cytokines With Diverse Functions in Gut Mucosal Immunity

Abstract: TL1A and its functional receptor DR3 are members of the TNF/TNFR superfamilies of proteins. Binding of APC-derived TL1A to lymphocytic DR3 provides co-stimulatory signals for activated lymphocytes. DR3 signaling affects the proliferative activity of and cytokine production by effector lymphocytes, but also critically influences the development and suppressive function of regulatory T-cells. DR3 was also found to be highly expressed by innate lymphoid cells (ILCS), which respond to stimulation by TL1A. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 123 publications
0
44
0
Order By: Relevance
“…However, TNFSF15 also exerts pro-inflammatory effects primarily by modulating T-cell and innate lymphoid cell activation via its role in adaptive immunity. 34 Further data have suggested that TNFSF15 might be a critical mediator of intestinal fibrosis, dependent on the intestinal microbiota, and suggested that targeting TNFSF15 might be a plausible approach for the treatment of CD and other inflammatory diseases. 35 , 36 Further studies are needed to elucidate such potential pathogenetic mechanisms and therapeutic potentials in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…However, TNFSF15 also exerts pro-inflammatory effects primarily by modulating T-cell and innate lymphoid cell activation via its role in adaptive immunity. 34 Further data have suggested that TNFSF15 might be a critical mediator of intestinal fibrosis, dependent on the intestinal microbiota, and suggested that targeting TNFSF15 might be a plausible approach for the treatment of CD and other inflammatory diseases. 35 , 36 Further studies are needed to elucidate such potential pathogenetic mechanisms and therapeutic potentials in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell activation and effective cytotoxicity are crucial weapons against tumors; however, they are frequently frustrated because of the dysfunction of T-cell functions [33,34]. As a general concept, the activation of antigenspecific T cells requires TCR recognition and costimulatory and coinhibitory molecules to deliver positive or negative signals [35,36]. In 2001, B7-H3 was first discovered and cloned from a human dendritic cell cDNA library and showed 20%-27% amino acid sequence identity with other members of the B7 costimulatory family [10].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial and nonmicrobial antigens increase TL1A expression in mononuclear phagocytes such as DCs and macrophages within the intestinal lamina propria. The presence of IL1b, IL23, IL2, and the TL1A/DR3 signaling pathway resulted in ILC3 proliferation and increased IL22 levels [135].…”
Section: Inflammatory Bowel Disease (Figure 1)mentioning
confidence: 97%